2009
DOI: 10.1002/jso.21328
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive procedures—strategies to reduce postoperative morbidity and management of surgical complications with special emphasis on anastomotic leaks

Abstract: Cytoreduction and hyperthermic intraperitoneal chemotherapy (HIPEC) for the therapy of peritoneal carcinomatosis are associated with substantial morbidity and acceptable mortality. Patient selection, learning curve, patient warming, and reduced blood loss are the main factors to decrease morbidity. Morbidity is mostly associated with bowl fistulas and anastomotic leakages. Depending on the site of leaks they may be managed conservatively or by reoperation. For standardization of study reports on morbidity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Intraabdominal bleeding, bile leaks, pancreatitis, major wound infections, acalculous cholecystitis, mesenteric ischemia, mechanical intestinal obstruction are other surgical complications reported[2,4,31,41-43]. The reoperation rates following the procedure for various complications range from 0%-23%[2].…”
Section: Discussionmentioning
confidence: 99%
“…Intraabdominal bleeding, bile leaks, pancreatitis, major wound infections, acalculous cholecystitis, mesenteric ischemia, mechanical intestinal obstruction are other surgical complications reported[2,4,31,41-43]. The reoperation rates following the procedure for various complications range from 0%-23%[2].…”
Section: Discussionmentioning
confidence: 99%
“…PC patients are often denied surgery and sent for multiple cycles of systemic CHT, which shows only limited effects. They are referred to the surgeon only in case of bowel obstruction or perforation and are proposed for CRS plus IP-CHT only after the failure of several cycles of systemic CHT, by which time the cancer load is massive and patients are usually physically wasted: in this setting, there is little chance of obtaining a CC-0 operation; patients often require multiple peritonectomy procedures and multiorgan resections and are at maximum risk for perioperative complications [24]. Early referral to surgery should thus be encouraged, so that the tumor load is limited, a CC-0 resection is still possible with a reduced need for multiorgan resections, and the risk for complications is minimal.…”
Section: Selecting Patients For Crsmentioning
confidence: 99%
“…Patient selection and surgical quality are the most important factors in preventing postoperative complications [24]. Several factors are associated with risk of complications, including the number of anastomoses performed, the need for diaphragmatic resection, scald injuries to the bowel due to HIPEC, the toxicity of IP-CHT itself, and the number of blood transfusions required.…”
Section: Reducing Complications After Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported increased rates of ECF after C-HIPC, though limited widespread use of this procedure make rates variable. [24][25][26] In some cases, these patients will present with multiple ECF or ECF with an open abdomen, the so-called enteroatmospheric fistula, a truly complex management problem for everyone who is involved in the care of the patient. 2…”
Section: Cytoreductive Surgery and Intraperitoneal Hyperthermic Chemomentioning
confidence: 99%